Progression from unipolar depression to schizophrenia. (4th November 2016) - Musliner, Katherine L.; Munk‐Olsen, Trine; Mors, Ole; Østergaard, Søren D.
Abstract : Objective: To examine progression from unipolar depression (UD) to schizophrenia and to identify groups of UD patients at elevated risk for progression. Method: Historical prospective cohort study using data from Danish national registers. The sample included 71 932 individuals who received a diagnosis of UD in Denmark between January 1, 1995, and May 31, 2013. Analyses were conducted using Kaplan–Meier estimates and Cox regressions. Results: The 18.5‐year cumulative incidence of schizophrenia was 5.5% in women and 8.4% in men. The strongest predictors of progression included younger age (adjusted hazard ratio (AHR) for individuals 18–24 vs. 40+ = 7.42, 95% confidence interval = [6.29, 8.74]), psychotic symptoms at index UD diagnosis (AHR = 3.70 [3.18, 4.31]), previous disorder with psychotic features (AHR = 3.71 [3.31, 4.16]), and previous illicit substance use disorder (AHR = 1.66 [1.40, 1.97]). Groups of UD patients with different combinations of risk factors had elevated risk for progression, with 10‐year cumulative incidences ranging from 9% to 62%. To conclude, at the time of UD diagnosis, the strongest risk factors for progression to schizophrenia include male sex, younger age, past/current psychotic symptoms, and illicit substance use disorders. These clinical predictors may aid in targeting monitoring for schizophrenia among patients with UD.